The effects of UV light and weather on plastics and elastomers - Massey, Liesl K. (PDL handbook series., 2007)
This extensively updated, comprehensive databook was created for design and application engineers, scientists, and material producer technical support and research and development personnel. Important weathering characteristics and material properties of plastics and elastomers are presented in discussion, tabular and graphical sections. It provides a ready reference for comparing materials in the same family as well as materials in different families. Data are presented on 80 major plastic and elastomer materials, including biodegradable or organic polymers. New to this edition, the resin chapters each contain textual summary information including category, general description, and weathering properties detailing information of the material's susceptibility or immunity to weathering including discussion of test results. Extensive references are provided. The resin chapter material supplier trade name product data are presented in graphical and tabular format, with results normalized to SI units, retaining the familiar format of the 1st edition and allowing easy comparison between materials and test conditions.